A high-efficiency actuator with great photoinduced force based on a bioinspired gradient design. Issue 23 (6th June 2022) - Liu, Mingxia; Xu, Zhao; Lv, Yimei; Zhu, Shu; Liu, Weiping; Yang, Lili; Ge, Dengteng
Abstract : Inspired by natural gradient functional materials, a gradient design of a photothermal component is developed to achieve a high-accuracy actuator with great photoinduced force. Abstract : Owing to the remote activation, spatiotemporal control and local response, photo-driven actuators have attracted great attention in diverse potential applications. However, actuators always suffer from weak deformation force or low-efficiency deformation. Inspired by natural gradient functional materials, a gradient design of a photothermal component is developed to achieve a high-efficiency actuator with great photoinduced force. Based on theoretical calculations of silver nanowires (AgNWs) in poly(ethylene- co -vinyl acetate) (EVA) elastomers, a uniform temperature distribution is achieved under irradiation. The high efficiency of this actuator with a recovery rate of ∼97% is attributed to the very little thermal stress. This inspired gradient strategy can be a versatile and effective route to the design of light-driven smart materials for broader applications with higher efficiency and better durability.